The Concept of The Art of Poetics According to Aristoteles - Laelina, Tri (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The art of poetry has its concept, which is to have poetic words so that someone can work hard to create joy. Aristotle has a statement that this art is very useful because the art of poetry can be used by people in differentiating the composition of poetry. There are three genres, namely, tragic poetry, comedy poetry, and idol poetry. Therefore, the art of poetry is an art that contains a human being having a plan for an imaginary representation (fact) of every occurrence of certain things. This research method uses a literature study. Collecting data through documentation, and analyzing the contents of the book.